1997
DOI: 10.1073/pnas.94.5.1902
|View full text |Cite
|
Sign up to set email alerts
|

The antigen-binding domain of a human IgG-anti-F(ab′)2 autoantibody

Abstract: Recent studies revealed an immunoregulatory role of natural IgG-anti-F(ab) 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 56 publications
5
45
0
Order By: Relevance
“…Mutation analysis performed with our phage Abs revealed that 40 -50% of the V H and V L genes coding for the Abs in both patients showed evidence of somatic hypermutation, supporting the idea that a significant part of the anti-␣ IIb ␤ 3 response developed in AITP or GT patients is driven by Ag. Our results confirm recent experiments where phage display was successfully used to isolate Abs from individuals with demonstrable serum Ab responses to a variety of Ags, including infectious agents such as HIV-1 (17), mutated protein in malignancy (18), and self Ags in autoimmune diseases (12)(13)(14)(15)(16)19). Isolated Abs have been shown to reflect the in vivo Ab response, and, even if theoretically, the combinatorial approach implies the possibility of pairings of L and H chains not present in the original source tissue.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Mutation analysis performed with our phage Abs revealed that 40 -50% of the V H and V L genes coding for the Abs in both patients showed evidence of somatic hypermutation, supporting the idea that a significant part of the anti-␣ IIb ␤ 3 response developed in AITP or GT patients is driven by Ag. Our results confirm recent experiments where phage display was successfully used to isolate Abs from individuals with demonstrable serum Ab responses to a variety of Ags, including infectious agents such as HIV-1 (17), mutated protein in malignancy (18), and self Ags in autoimmune diseases (12)(13)(14)(15)(16)19). Isolated Abs have been shown to reflect the in vivo Ab response, and, even if theoretically, the combinatorial approach implies the possibility of pairings of L and H chains not present in the original source tissue.…”
Section: Discussionsupporting
confidence: 87%
“…Combinatorial libraries from immune donors have been often used to determine the nature of the humoral immune response, for example, in patients with autoimmune or neoplastic diseases or with viral infection (12)(13)(14)(15)(16)(17)(18)(19). Nucleotide sequences of variable regions of such Abs may help us to understand the origin of the secreting B cells.…”
mentioning
confidence: 99%
“…The preferential autoantibody binding of IgG3 to peptides oriented with free C-termini differed from a previous and detailed epitope analysis (54). That work showed that two recombinant, human, single-chain Fvs with anti-hinge specificity were bound to multiple synthetic double-chain peptides (and variants) containing the core C-P-P-C hinge sequence with a free N terminus corresponding to threonine 223 in the upper IgG1 hinge (54,55). Nevertheless, when tested on actual fragments of IgG, those same two scFvs exhibited primarily anti-F(abЈ) 2 reactivity with little or no anti-Fc binding (in accord with our own findings with serum IgG3) (55).…”
Section: Discussionmentioning
confidence: 49%
“…That work showed that two recombinant, human, single-chain Fvs with anti-hinge specificity were bound to multiple synthetic double-chain peptides (and variants) containing the core C-P-P-C hinge sequence with a free N terminus corresponding to threonine 223 in the upper IgG1 hinge (54,55). Nevertheless, when tested on actual fragments of IgG, those same two scFvs exhibited primarily anti-F(abЈ) 2 reactivity with little or no anti-Fc binding (in accord with our own findings with serum IgG3) (55). The authors concluded through additional peptide binding approaches that human serum IgG and IgA anti-hinge autoantibodies most likely bound to conformational epitopes in the hinge (26,34).…”
Section: Discussionmentioning
confidence: 99%
“…(1) using the PCR primer set described by Welschof et al (2). The library, with a calculated complexity of 2 x 107 independent clones, was constructed in pSEX81 ( Fig.…”
Section: Bodymentioning
confidence: 99%